Expression of the Cavin Family in Childhood Leukemia and Its Implications in Subtype Diagnosis and Prognosis Evaluation - Yang, Jing; Huang, Junbin; Wang, Huabin; Liu, Yong; Tang, Yanlai; Lin, Chao; Zhou, Qin; Chen, Chun (Frontiers in Pediatrics, 2022)
Background Caveolae are plasma membrane subdomains of many mammalian cells that play critical roles in cellular processes, including endocytosis, signal transduction and tumorigenesis. Cavin proteins are essential for caveola formation, structure and function and are reported to be involved in various human diseases, but little is known about their expression and prognostic value in leukemia. Methods We performed a detailed analysis of Cavin family mRNA expression levels in different cancer tissues vs. normal tissues via the ONCOMINE, Gene Expression Profiling Interactive Analysis (GEPIA) and Cancer Cell Line Encyclopedia (CCLE) databases. Then, we used qRT-PCR and Western blotting to validate Cavin1-4 expression in 10 fresh leukemia samples. Moreover, we estimated their prognostic value in leukemia with the R programming language and GEPIA database. Results The expression of Cavin members is low in most human cancers, especially in leukemia. Cavin-1 and Cavin-2 are often more expressed in myeloid leukemia than lymphoblastic leukemia, but Cavin-4 has the opposite pattern. Interestingly, low expression of CAVIN1 and CAVIN4 is correlated with poorer outcome but low CAVIN2 expression is associated with a significantly better leukemia prognosis in leukemia. Conclusion The Cavin family showed significant expression differences between leukemia and normal cells. High Cavin-2 and low Cavin-4 levels predict poor survival and could be promising subtype diagnosis and prognosis biomarkers for leukemia.